Balancing Justice and Tradition: An Islamic Legal Perspective on Constitutional Court Rulings Regarding Marriage Age - Ahmad Izzat Fannani; Amran Khaliqurrahman; Isla Rania (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2024)
This study analyzes the Constitutional Court Decision Number 22 / PUU-XV / 2017 related to the age limit of Marriage from the perspective of Islamic law. The change in the marriage age limit in this law was passed based on the decision of the Constitutional Court of the Republic of Indonesia (MK) Number 22 PUU-XV/2017, which was born due to the controversy over the previous marriage law. This is a literature research by re-analyzing the policy content of the Constitutional Court of the Republic of Indonesia Number 22/PUU/XV/2017 decision. The analysis examines the legal basis, the applicant's legal standing, and the decision's relevance to Islamic law principles. The results showed that the Constitutional Court's decision was based on valid legal standing and rational arguments. This decision is in line with the value of Islamic law in paying attention to maslahah (benefit). Still, there are differences in certain methodological aspects, especially in the maslahah mursalah approach. The findings also reveal that the change in the marriage age aims to reduce discrimination against women and protect their health, education, and socio-economic rights. From the perspective of Islamic law, the minimum age of Marriage is ijtihadiyah and can be adjusted to the context of the times, as the principle of maqashid al-shari’ah is oriented towards the welfare of the people. This research recommends further harmonizing Islamic and national law to create fairer and more applicable rules.